The Algol-type eclipsing binary TZ Eridani: BV photometry and search for pulsations and tertiary component - Liakos, A.; Ulas, B.; Gazeas, K.; Niarchos, P. (Communications in Asteroseismology, 2008)
CCD photometric observations of the Algol-type eclipsing binary TZ Eri have been obtained in B and V filters during 26 nights from December 2007 to February 2008 at the Athens University Observatory. The light curves are analyzed with the Wilson-Devinney code, new geometric and photometric elements are derived, a time series analysis of the observations is applied and a multiperiodic behavior is also discussed. The presence of a third light in the system is considered and our results are compared with those of the O-C analysis for a third body in the system, given by Zasche et al. (2008).